Elements of Smart Computer Graphics – A Potential Basis for New Experimental Method of Teaching and Learning - Bernátová, Renáta; Bernát, Milan; Poráčová, Janka; Rudolf, Ladislav; Kľučarová, Andrea (International Journal of Emerging Technologies in Learning (iJET), 2020)
This paper outlines the possibilities of implementing the elements of smart computer graphics (applets and animations) into the curriculum of science-oriented school subjects. Applet is a purposeful (especially educational) program, which was developed on the platform of modern elements of smart computer graphics. These elements allow us to visualize technical and natural objects, phenomena or processes in such a degree of clarity which cannot be achieved by traditional ways of visualisation or by using traditional technological techniques. To be more specific, thanks to computer animations and simulations it is possible to slow down, speed up or shred the processes over time as well as phenomena taking place in natural systems. Moreover, we are able to visualize objects that cannot be seen with the naked eye because of their size (too small or too large), inaccessibility to humans or, in fact, their non-existence. Application components called Interactive Computer Graphics (hypertext, drag and drop, etc.) as well as Flash animations included into the teaching-learning process are together with a comprehensive methodology of their application, a part of newly designed teaching method. The efficiency of this method is verified by pedagogical experiment.